Effects of bicycle frame ergonomics on triathlon 10-km running performance - Garside, I.; Doran , D. A. (Journal of Sports Sciences, 2000)
It is perceived that, during the triathlon or duathlon, cycling with a steep (>76°) rather than a shallow (<76°) frame geometry might attenuate the fatigue associated with progression from the cycle to run disciplines and improve subsequent 10-km running performance. This is based on anecdotal testimony from athletes purporting to have experienced improved performance; no empirical evidence exists. To evaluate this view, eight male triathletes completed a counterbalanced, 40-km cycle ride at two frame geometries (73° and 81°) at ~70% VO2peak. Immediately after completion of each 40-km cycle, a self-paced 10-km treadmill time trial was undertaken, during which physiological, kinematic and performance variables were measured. The 10-km run performance (mean ± s: 42:55 ± 4:19 vs 46:15 ± 4:52 min; P < 0.01) and combined cycle and run performance (1:45:49 ± 5:45 vs 1:50:33 ± 6:08; P < 0.001) were faster in the 81° than the 73° condition. Improvements in performance were most prominent during the first 5 km of the run (21:41 ± 2:15 vs 24:15 ± 2:31 min in the 81° and 73° conditions respectively). These improvements were not evident during the second 5 km of the run. No differences in physiological variables were noted, although heart rate, stride length and stride frequency were increased during the 81° condition (P < 0.05). Modifying frame geometry from a seat tube angle of 73° to 81° improves 10-km running and combined cycle plus run performance. These improvements in performance might relate to alterations during the cycling phase, which minimizes the 'residual effect' of this (i.e. the adverse changes in substrate availability, thermoregulatory, cardiovascular and biomechanical factors felt immediately after transition from cycling to running) and attenuates negative changes in physiological and kinematic responses during the 10-km run.